Purchase intention of foreign products: a study on Bangladeshi consumer perspective - Haque, A. K. M. Ahasanul; Anwar, Naila; Yasmin, Farzana; Sarwar, Abdullah; Ibrahim, Zariyah; Momen, Abdul (SAGE Open, 2015)
The current research aims to investigate various factors that influence consumers’ intention of buying foreign products. The data were collected by means of self-structured questionnaires from a total of 260 Bangladeshi consumers residing in the two major cities of the country, Dhaka and Chittagong. At the initial stage, statistical analyses, particularly descriptive analysis as well as exploratory factor analysis, were conducted using SPSS, after which structural equation modeling was run by using AMOS. The findings have established that brand image and quality of foreign products carry significant positive influence on purchase intention of foreign products. However, religiosity leaves a significant negative effect on the purchase intention of foreign products. Furthermore, findings have also revealed that the image of the country of origin carries a significant positive effect on brand image but ethnocentrism carries a significant negative effect on perceptions about the quality of foreign products in their purchase intention. The major contribution of the current study is that it focuses on Bangladesh, as there is a vacuum in contemporary literature on this topic in the context of Bangladeshi consumers. The findings derived from the study could facilitate marketers in the creation of effective marketing strategies and at the same time are also valuable for academicians as well as consumers at large.